24 Measuring the value of endoscopic retrograde cholangiopancreatography (ERCP) activity: an opportunity to stratify endoscopists based on their value. (5th April 2017) - Parihar, V; Moran, C; Maheshwari, P; Kumar, S; Keohane, J; Sengupta, S; Hall, B; Cheriyan, D; O'Toole, A; Murray, F; Patchett, S; Harewood, G
Abstract : Background: The value in healthcare can be defined as patient health outcomes achieved per monetary unit spent. Aim: To characterise the value of ERCP performance of four gastroenterologists. Method: Medical records of patients undergoing ERCP between September 2014 and September 2016 in an academic medical centre were reviewed; all procedures were performed by one of four experienced gastroenterologists, all of whom have performed at least 1000 ERCPs. Procedure value was defined as the quality of procedure (Q) divided by the duration of procedure (T) adjusted for complexity level (C), that is, Q/(T/C). In those patients undergoing multiple ERCPs during the study period, only the index procedure was considered for analysis. ERCP quality and complexity were both graded on a 1 to 4 Likert scale based on American Society for Gastrointestinal Endoscopy (ASGE) criteria; time was recorded (in minutes) from intubation to extubation. Although individual components of procedure cost (eg, ERCP accessories, patient sedation, etc.) were not itemised, the procedure duration (ie, the cost of endoscopist's time) was considered to be a reliable surrogate estimate of overall procedure cost. Results: In total, index procedures on 465 patients were performed over 24 months; mean of 116 index ERCPs per endoscopist. Mean quality varied from 2.25 to 2.53 while adjusted mean duration (T/C) varied from 22.13 to 28.66 min per procedure. Value measurements varied from 8.1 to 10.7. Conclusions: There was a 32% variation in the value of endoscopist activity. As healthcare costs are scrutinised more closely, such value measurements are likely to become more relevant.